Less alimony after divorce: Spouses' behavioral response to the 2008 alimony reform in Germany - Julia Bredtmann; Christina Vonnahme (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The 2008 alimony reform in Germany considerably reduced post-marital and caregiver alimony. We analyze how individuals adapted to these changed rulings in terms of labor supply, the intra-household allocation of leisure, and marital stability. We use the German Socio-Economic Panel (SOEP) and conduct a difference-in-difference analysis to investigate couples' behavioral responses to the reform. The results do not confirm theoretical expectations from labor supply and household bargaining models. In particular, we do not find evidence that women increase their labor supply as a result of the negative expected income effect. Neither do our results reveal that leisure is shifted from women to men as a response to the changed bargaining positions. In contrast, we find evidence that the reform has led to an increase in the probability to separate for married as opposed to non-married cohabiting couples. – – Die Unterhaltsrechtsreform in Deutschland, die 2008 in Kraft trat, senkte die Ansprüche auf Geschiedenen- und Betreuungsunterhalt deutlich. Wir analysieren, wie sich Individuen bezüglich ihres Arbeitsangebots, der Aufteilung von Freizeit innerhalb des Haushalts und der Stabilität von Partnerschaften an die veränderten gesetzlichen Rahmenbedingungen anpassten. Die empirische Analyse beruht auf Daten des Sozio-Oekonomischen Panels (SOEP) und einem Differenz-von-Differenzen-Ansatz. Die Ergebnisse können theoretische Erwartungen, die aus Arbeitsmarkt- und Intra-Haushalts-Verhandlungsmodellen abgeleitet werden, nicht bestätigen. Insbesondere gibt es keine Evidenz dafür, dass Frauen ihr Arbeitsangebot in Folge der Reform und der damit verbundenen negativen Einkommenseffekte erhöhen. Auch eine Verschiebung von Freizeit von Frauen zu Männern durch die veränderten Verhandlungspositionen scheint nicht stattgefunden zu haben. Jedoch zeigt sich, dass die Reform zu einem Anstieg der Trennungswahrscheinlichkeit von verheirateten relativ zu unverheiratet zusammenlebenden Paaren führte.
Keywords: J12; J13; J22; 330; alimony; marital instability; female labor supply; intra-household bargaining